Evaluation of the dispensation of antidepressants in primary health care in the city of Santiago – RS - Brum de Freitas, Brunnella; Fontella Cocentino, Fernanda; Avila Monte, Mariana; Leitão Gindri, Amanda; Pedrolo Canterle, Liana; Urach Monteiro, Danieli; Molz de Freitas, Catiuscia (Seven Editora, 2023)
Introduction: The Coronavirus disease-19 (COVID-19) pandemic has generated significant impacts both economically and socially, as well as on the physical and mental health of the general population, causing an increase in depression, anxiety and stress. Depression is considered a multifactorial disorder that involves biological, psychological and social aspects and has become a relevant and growing public health problem. It is noteworthy that the pharmacological treatment for this pathology includes the use of antidepressant drugs, many of which are available in the Unified Health System (SUS). In this sense, it is worth mentioning that, in Brazil, there are still few studies evaluating the impact of the pandemic on the consumption profile of antidepressant drugs in the population. Objective: The objective of this work was to analyze the impact of the COVID-19 pandemic on the distribution of antidepressants in primary care in the municipality of Santiago, in Rio Grande do Sul. Methodology: To carry out this research, a survey of antidepressant drugs dispensed at the Basic Pharmacy of SUS in the city was carried out. Based on information contained in the Integrated Health Services Management System (SIGSS), used in the distribution management and stock control of the Basic Pharmacy, data referring to the three-year period, from March 2019 to March 2019, were analyzed. 2022. Results and Discussion: It was possible to observe an increase of 38.10% in 2020 and 115.47% in 2021 in the dispensation of antidepressant drugs, in relation to the year 2019. In addition, it was verified that the female gender presented higher rate of consumption of antidepressants, corresponding to the percentage of 77.59% in relation to males. The drug fluoxetine 20 mg was the most used drug, totaling 50.89% of dispensations during the three years, where predominantly users are aged between 46 and 60 years. Amitriptyline 25mg corresponded to 30.28% and Imipramine 25mg represented 9.33% of dispensations, both from the tricyclic antidepressant class. It is noteworthy that users of this class of medication are mostly elderly people over 61 years old. Furthermore, it was possible to observe an increase of 134.68% in the dispensations of selective serotonin reuptake inhibitors (SSRIs), 78.15% in tricyclic antidepressants and 1002.5% in atypical antidepressants during the pandemic period compared to the year 2019 , pre-pandemic period. Conclusion: It can be concluded that the pandemic had an impact on the consumption of antidepressants by the Santiaguense population served by the Basic Pharmacy. Still, the results found in this work may help in the planning of strategies that can collaborate with issues related to the mental health of the population and the consumption of antidepressants, seeking the rational use of this class of medication. DOI: https://doi.org/10.56238/devopinterscie-130